FINANCIAL DISTRESS IN TRANSPORTATION AND LOGISTIC COMPANIES IN INDONESIA : COMPARATIVE STUDY OF THE COVID-19 PANDEMIC CRISIS - Eka Frema Hidayati; Wiwit Hariyanto (Antis Publisher, 2025)
Objective: This study aims to analyze the differences in the level of financial distress among transportation and logistics sompanies in Indonesia between the periode during the pandemic Covid-19 (2020-2021) and after the pandemic Covid-19 (2022-2023). Method: The research sample consisted of 30 companies that met the criteria using purposive sampling techniques. The method use id a quantitative approach with descriptive statistical analysis, normality testing, and a mean difference test. Results: The result show that there is a significant difference between the two periods, with a significant value 0f 0,034 < 0,05. The average level of financial distress increased after the pandemic, accompanied by a decrease in standard deviation, indicating improvements and greater stability in the financial condition of companies post-pandemic. Novelty: These findings support signaling theory, in which changes in a company’s financial condition reflect positive or negative signals to the market and stakeholders.